The significance of arbutin and its derivatives in therapy and cosmetics. (September 2015) - Migas, Piotr; Krauze-Baranowska, Mirosława
Graphical abstract: Highlights: The methods for preparation of arbutin and its derivatives are discussed. The antibacterial activity of arbutin and the use of arbutin-containing plants in the treatment of urinary tract infections are highlighted. The anti-melanogenic activity of arbutin and its derivatives are described in detail. The antioxidant, anti-inflammatory and antitumor activities of arbutin and its derivatives are also considered. Abstract: The ongoing studies on biological activity of arbutin and its derivatives show a wide range of their possible applications. Arbutin containing plant substances are used mostly in the treatment of urinary tract infections (UTI). However, several in vitro and in vivo studies revealed anti-melanogenic activity of arbutin, which can be useful in hyperpigmentation therapy. Moreover, it was found that the modifications in arbutin structure lead to an increase of the above-mentioned activity. The lack of significant adverse effects of arbutin and its derivatives makes them a valuable alternative to hydroquinone. Therefore, an increasing interest in arbutin and its derivatives is observed especially in the cosmetics industry. The scope of biological activity covered by the findings of in vivo and in vitro studies on arbutin and its derivatives are discussed.